2013
DOI: 10.2166/wst.2013.781
|View full text |Cite
|
Sign up to set email alerts
|

Novel catalytic and mechanistic studies on wastewater denitrification with hydrogen

Abstract: The present work reports up-to-date information regarding the reaction mechanism of the catalytic hydrogenation of nitrates in water media. In the present mechanistic study, an attempt is made, for the first time, to elucidate the crucial role of several catalysts and reaction parameters in the mechanism of the NO(3)(-)/H(2) reaction. Steady-state isotopic transient kinetic analysis (SSITKA) experiments coupled with ex situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) were performed on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…This fact was later confirmed by Theologides et al [48,113], who concluded that the production of ammonium could be decreased by up to three times when 20 vol% of air is added to the gas fed to the fixed bed catalytic reactor.…”
Section: Continuous Reactorsmentioning
confidence: 73%
“…This fact was later confirmed by Theologides et al [48,113], who concluded that the production of ammonium could be decreased by up to three times when 20 vol% of air is added to the gas fed to the fixed bed catalytic reactor.…”
Section: Continuous Reactorsmentioning
confidence: 73%
“…243 The results pointed out that both the presence of TiO 2 in the support and the presence of oxygen in the feed stream enhance the formation and adsorption of different active Nintermediates on the support or on the surface of Pd−Cu catalysts. In addition, it has been found that Cu clusters increase the reduction rate of nitrates.…”
Section: Ssitka Coupled With Spectroscopic Techniquesmentioning
confidence: 98%
“…The actual metal loading of Ag/Al 2 O 3 was found to be 0.97 wt%, whereas its total surface area (BET) was found to be 194.3 m 2 g −1 . The Ag dispersion value was determined by a modified H 2 chemisorption method as 0.23 …”
Section: Resultsmentioning
confidence: 99%
“…The modification of the method was made in order to eliminate any possible hydrogen spillover phenomena, which are common in metal‐supported catalysts. The exact procedure followed is described in detail elsewhere …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation